Therapeutic potential of IGF-I on hippocampal neurogenesis and function during aging - Morel, Gustavo Ramón (2016)
In rats, learning and memory performance decline during normal aging, which is paralleled by a severe reduction of the levels of neurogenesis in the hippocampal dentate gyrus (DG). A promising therapeutic strategy to restore neurogenesis in the hippocampus of old rats and their spatial memory involves the use of insulin-like growth factor-I (IGF-I). The peptide exerts pleiotropic effects in the brain, regulating multiple cellular processes. Thus, 4-week intracerebroventricular (ICV) perfusion of IGF-I significantly restored spatial memory and hippocampal neurogenesis in old male rats. Similar results were achieved by ICV IGF-I gene therapy in aging female rats. Thus, the treatment seemed to increase the number of immature neurons in the DG of 28 mo old rats, which was paralleled by an increase in the accuracy of the animals to remember specific patterns, which is known as pattern separation memory. The DG is thought to be the main hippocampal structure involved in pattern separation memory and there is evidence that the level of neurogenesis in the DG is directly related to pattern separation performance in rodents. Summing up, IGF-I emerges as a promising restorative molecule for increasing hippocampal neurogenesis and memory accuracy in aged individuals and possibly, in neurodegenerative pathologies.